STRENGTHENING ENVIRONMENTAL CARE CHARACTER THROUGH PROJECT-BASED LEARNING IN PANCASILA EDUCATION IN ELEMENTARY SCHOOLS - Apriani, Dini; El widdah, Minnah; Fatmawati, Kiki (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to enhance students’ environmental care attitudes through the implementation of the Project-Based Learning (PBL) model in Pancasila Education for fifth-grade students at State Elementary School 29/VII Lubuk Sayak. The research employed a classroom action research approach using the Kemmis and McTaggart model, conducted in two cycles, each consisting of planning, action implementation, observation, and reflection stages. The research subjects comprised 19 students. Data were collected through observations, an environmental care attitude questionnaire, and documentation. Data analysis was carried out using descriptive quantitative and qualitative methods. The results indicate a significant improvement in students’ environmental care attitudes. In the pre-cycle stage, the percentage of mastery of environmental care attitudes was 35%, categorized as low. After the implementation of Project-Based Learning in Cycle I, the mastery percentage increased to 70%, categorized as fairly good. Furthermore, in Cycle II, the mastery percentage reached 95%, categorized as very good. This improvement was accompanied by increased student learning activities and teacher teaching activities, which reached 92.5% in Cycle II. These findings demonstrate that the Project-Based Learning model is effective in enhancing elementary school students’ environmental care attitudes through contextual, collaborative, and character-oriented learning. Therefore, Project-Based Learning can be considered an alternative instructional model in Pancasila Education to strengthen environmental care character in accordance with the values of the Pancasila Student Profile.